City shape, commuting time and workplace choice: Analyzing urban spatial form in China - FU, Shen (Institutional Knowledge at Singapore Management University, 2024)
This paper investigates the relationship between city shape, commuting time, and workplace choice within the context of Chinese cities. Using an urban form measure, nCohesion, and nighttime light data, I constructed the China City Shape Database for 263 Chinese cities. The empirical analysis reveals a counterintuitive finding: cities with less compact shapes, despite having longer within-city distances, are associated with shorter commuting times. This is because residents in poorly shaped cities tend to select workplaces closer to their homes to mitigate commuting difficulties. The findings suggest that improving city shape alone may not reduce commuting times; instead, enhancing transportation infrastructure and promoting local employment can mitigate the adverse effects of poor city shapes.